PENGARUH VIRAL MARKETING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SKINCARE CAMILLE BEAUTY - Aisah, Nur; Permana, Budi (STKIP Persada Khatulistiwa Sintang, 2023)
The fact of the rise of social media and the strong development of digital has made some entrepreneurs or business people to compete with each other to develop a product, with the trend that is developing today. This study aims to determine how much influence viral marketing and product quality have on purchasing decisions, this type of research is quantitative descriptive with an associative approach and uses multiple linear regression analysis. The sample in this study was consumers who used Camille beauty skincare which was determined using the calculation of the Slovin formula with alpha 5% and the results were 96 respondents. The sampling technique used in this study is probability sampling with a simple random sampling approach. Data analysis uses multiple linear regression, partial and simultaneous hypothesis testing and coefficient of determination. The results of this study show that simultaneously, viral marketing variables and product quality have a positive and significant effect on purchasing decisions while partially, viral marketing variables and product quality have a positive and significant effect on purchasing decisions.